Identification of massive sulphide targets using the galvanic source EM signal from a sub-audio magnetic survey at the Far South project, Western Australia. Issue 3 (1st September 2016) - Card, Daniel; Wallace, Yvonne; Peters, Bill
Abstract : The Far South project is located 5 km south along strike from the Deep South mine, where gold mineralisation is commonly associated with semi-massive pyrrhotite and pyrite. Data from a sub-audio magnetic (SAM) survey, set up in galvanic configuration, were acquired over the project principally to map stratigraphy and structure using the on-time magnetometric conductivity (MMC) and total magnetic intensity (TMI) responses. The off-time galvanic source electromagnetic (GSEM) data were subsequently extracted from the raw data and four late-time anomalous responses were identified. Two of these responses are strong late-time anomalies up to 350 m in strike length, clearly visible in the 60 ms time gate, and the remaining two are weaker mid-time, subtler and less diagnostic responses. Modelling of the GSEM responses was attempted using conventional electromagnetic (EM) modelling techniques, where certain assumptions had to be made for the survey geometry and current path. The assumed current path has an effect on the coupling of the inducing current with the target, so in order to validate the assumptions and GSEM modelling results, follow-up moving-loop and fixed-loop electromagnetic (MLEM and FLEM) surveys were required. These surveys confirmed well-defined conductive responses over all four follow-up areas. Modelling of the GSEM data over the two strongest anomalies is in good agreement with modelling of the MLEM/FLEM data. Modelling at a third target showed some similarity to results obtained by modelling the follow-up EM survey data, and one target was not defined clearly enough in the GSEM data to allow modelling and had to be modelled solely on the follow-up FLEM data. The results of these efforts confirm the ability to identify and produce a reasonably useful model of strong conductive targets from SAM GSEM data, indicating that the rapid acquisition SAM system is an effective tool for quick reconnaissance in sulphide exploration. Subsequent drilling identified sulphide mineralisation at all four conductors. Abstract : Data from the Far South project were acquired using a sub-audio magnetic (SAM) survey, set up in galvanic configuration. The galvanic source electromagnetic (GSEM) data were used to identify conductive responses. Modelling of the GSEM responses was attempted with some success, showing this method to be an effective reconnaissance tool.